"Political Correctness" als Kern der Politik : : mit Nietzsche gegen die neue Rechte - Schubert, Karsten (2020)
Abstract: The article develops the concept of „political judgement“ – a new, affirmative understanding of the phenomena which are criticized as „political correctness“ by both right-wing and liberal commentators. To that end, it takes the right’s claims, that „political correctness“ is slave morality in Nietzsche’s sense seriously and proposes a systematic reading of a right-nietzschean position. Connecting current „political-correctness“-critique and Nietzsche in this way allows for a deeper understanding of the right-wing rationality and the affective energy underlying the critique. Through contrasting this right-nietzschean reading with its systematic opposite, a left-nietzschean position, the article shows that the essence of politics is to redesign norms which distribute privilege. What is critically labelled „political correctness“ is, thus, better captured by the notion of „political judgment“, because – given an interest in emancipation – such politics should not be demonized when they limit the freedom provided by undeserved privileges